Rancang Bangun Sistem Informasi Donasi Berbasis Web Menggunakan Metode Waterfall di Yayasan Al-Hayah Hayatuna - Rizki Aditya; Dea Safitri; Fiqri Nurhidayat; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2026)
Donation management at Yayasan Al-Hayah Hayatuna is still carried out manually. This condition causes several problems, including unstructured data recording, difficulty in finding donation history, delays in preparing reports, and limited delivery of information to the public. This project aims to design and develop a web-based donation information system to improve donation management and reach more potential donors. Data were collected through observation, interviews with the foundation’s management, and literature studies. The system was developed using the Waterfall method, which included requirement analysis, system design, implementation, testing, and evaluation. The system was built using PHP Native, HTML, CSS, JavaScript, Bootstrap, MySQL, and XAMPP. Functional testing was conducted using the Black Box Testing method. The developed system provides features for account registration, login, donation programs, donation forms, payment confirmation, donation history, donor data management, campaign management, donation reports, and logout. Testing of ten scenarios showed that all system features worked successfully and were declared valid. The web-based system helps the foundation manage donation data in a more structured and computerized manner. It also improves data searching and report preparation, reduces manual recording errors, and supports wider and more transparent publication of donation programs.